The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1016/j.jep.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic properties of Orthosiphon stamineus Benth

Abstract: O. stamineus exhibited diuretic activity, but was less potent than furosemide and hydrochlorothiazide. Care should be taken when consuming this herb as slight increase of kidney function enzymes was recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 17 publications
0
41
0
3
Order By: Relevance
“…The recommended daily dose in folk medicine is at least 6-10 times lower than the highest daily dose tested in mice in this study (i.e., 500-4000 mg/kg body weight po). It is of note that these doses were comparable to or higher than those reported to induce pharmacological effects in rodents such as anti-ulcer effects in rats (125-1000 mg/kg body weight) (Yam et al, 2009), diuretic effects in rats (5-10 mg/kg body weight po) (Adam et al, 2009), and anti-inflammatory and analgesic effects in rats and mice (500-1000 mg/kg body weight po) (Yam et al, 2008).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The recommended daily dose in folk medicine is at least 6-10 times lower than the highest daily dose tested in mice in this study (i.e., 500-4000 mg/kg body weight po). It is of note that these doses were comparable to or higher than those reported to induce pharmacological effects in rodents such as anti-ulcer effects in rats (125-1000 mg/kg body weight) (Yam et al, 2009), diuretic effects in rats (5-10 mg/kg body weight po) (Adam et al, 2009), and anti-inflammatory and analgesic effects in rats and mice (500-1000 mg/kg body weight po) (Yam et al, 2008).…”
Section: Discussionmentioning
confidence: 62%
“…In Sprague-Dawley rats, an acute oral toxicity study found no mortality and no overt toxicity up to the highest dose of Orthosiphon stamineus extract tested (LD 50 > 5000 mg/kg body weight po) (Abdullah et al, 2009), while a 14-day repeated dose study found no deaths and no other adverse effects on females treated orally with doses of Orthosiphon stamineus extract ranging from 500 up to 5000 mg/kg body weight/day (Chin et al, 2008). In addition, pharmacological studies of Orthosiphon stamineus extracts have not revealed any adverse effect on rats and mice either (Adam et al, 2009;Beaux et al, 1999;Yam et al, 2008Yam et al, , 2009. Considering the lack of overt toxicity in the aforementioned rodent studies and in a preliminary experiment with Swiss Webster mice, 4000 mg/kg of body weight/day (for 3 days) was set as the upper limit of the dose range tested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly considerable attention has been given to its antioxidant, anti-inflammatory, diuretic, antihyperglycemic, hypouricemic, hepatoprotective and anti-fungal properties (Sriplang et al, 2007;Yam et al, 2007;Yam et al, 2009;Yam et al, 2010;Mohamed et al, 2011a;Pan et al, 2011). OS extracts also exhibited diuretic activity via increase of urine volume and electrolytes (Na þ and K þ ) excretion in hyperuricemic rats (Arafat et al, 2008;Adam et al, 2009). Moreover, aqueous and 50% ethanol extracts of OS are low toxicity (Mohamed et al, 2011b;Muhammad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A number of research has also been done to explore the effects of the leave extract of Orthosiphon aristatus (OA) -commonly known as cat whiskers in Malay, or Java tea, on urolithiasis (Yam et al, 2013;Abdelwahab et al, 2011;Adam et al, 2009;Yam et al, 2007). These studies focused on the medicinal properties of OA.…”
Section: Introductionmentioning
confidence: 99%